(untitled) (Kronika Bydgoska, 2010)
Walk The Wild Road, an adventure and historical novel for young people by English writer Nigel Hinton, was published in the USA at the beginning of 2011. This is an attempt at showing the history of the authofs grandfather, who was born in the area of present-day Poland in Polichno near Nakło, Wilhelmsdorf at that time, in 1858. Georg Leo Hinz ran away from home as a 12-year-old boy and reached on foot the sea, where he embarked on a ship. Several times he sailed around the globe before he settled in London permanently and quit sailing. Nigel Hinton’s book presents the travel of the young boy through our region: several chapters are devoted to his stay in Bydgoszcz, where Leo leams to eam his living, to steal and... where he gets drunk for the first time in his life.